2021
DOI: 10.3390/ijms22052236
|View full text |Cite
|
Sign up to set email alerts
|

Trogocytosis between Non-Immune Cells for Cell Clearance, and among Immune-Related Cells for Modulating Immune Responses and Autoimmunity

Abstract: The term trogocytosis refers to a rapid bidirectional and active transfer of surface membrane fragment and associated proteins between cells. The trogocytosis requires cell-cell contact, and exhibits fast kinetics and the limited lifetime of the transferred molecules on the surface of the acceptor cells. The biological actions of trogocytosis include information exchange, cell clearance of unwanted tissues in embryonic development, immunoregulation, cancer surveillance/evasion, allogeneic cell survival and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 166 publications
0
6
0
Order By: Relevance
“…In the past decade, trogocytosis (named from the ancient Greek trogo-, which means gnaw or nibble) has been attracting increasing attention in the vast fields of biology research, including immunology, microbiology, neurology, and developmental biology [1][2][3][4][5][6][7]. Trogocytosis is an active process, in which one cell rapidly acquires the fraction of another cell in a cell contact-dependent manner [8] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, trogocytosis (named from the ancient Greek trogo-, which means gnaw or nibble) has been attracting increasing attention in the vast fields of biology research, including immunology, microbiology, neurology, and developmental biology [1][2][3][4][5][6][7]. Trogocytosis is an active process, in which one cell rapidly acquires the fraction of another cell in a cell contact-dependent manner [8] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Further, trogocytosis is used by amoebae to kill host cells [ 12 , 13 ], indicating that this biological phenomenon is widely conserved throughout eukaryotes. Recent findings of trogocytosis in microbes [ 14 ], mammalian neuronal networks [ 15 , 16 ], and non-T cell immune cell interactions [ 2 , 17 , 18 ] have been well summarized by others previously and also in this issue. Thus, here we mainly focus on T cell trogocytosis and related diseases.…”
Section: Introductionmentioning
confidence: 93%
“…Specifically, several studies have utilized the ability of CD8 + T cells to acquire antigen peptide-MHCI complexes in order to detect antigen-specific T cells in peripheral blood mononuclear cells (PBMCs) from patients infected with human T-cell lymphotropic virus type I (HTLV-1) or lymphocytic choriomeningitis virus (LCMV). Tomaru et al first successfully identified T cell populations that specifically recognize the HTLV-I Tax (11)(12)(13)(14)(15)(16)(17)(18)(19) peptide presented on HLA-A*201 [131]. In this study, the authors established Hmy2.CIR cells, an HLA-A and HLA-B locus-defective immortalized B cell line, transduced with HLA-A*201 fused with GFP.…”
Section: Application Of Trogocytosismentioning
confidence: 99%
“…The molecules transferred via trogocytosis are functional and influence the response of the receiving cell, thus implying consequences for the modulation of immune responses. Therefore, trogocytosis represents an important process for cell-cell communication, immune regulation, and response to pathogens and cancerous cells ( Li et al., 2021 ; Miyake and Karasuyama, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as we will discuss, innate immune cells may employ prolonged trogocytosis to induce tumor cell death ( Matlung et al., 2018 ; Velmurugan et al., 2016 ). The contact between different types of immune cells via trogocytosis is a phenomenon also occurring in the TME as a strategy to modulate the function of immune cells, thus indirectly affecting cancer progression ( Li et al., 2021 ). In this respect, trogocytosis can be regarded as a double-edge sword in cancer immunity involved in both activation and repression pathways of immune responses to cancer.…”
Section: Introductionmentioning
confidence: 99%